Vrednote prostora kot integralni del izobraževanja - Resnik Planinc, Tatjana (Geografski vestnik, 2006)
In the article the meaning of education for sustainable development and its goals are presented. Values are an integral part of education. New ways of education regarding space related topics in primary and secondary schools across Europe should be found. The article deals with the results of an international survey, which aim was to define the main preferences and obstacles, sensed by teachers and their pupils, from the viewpoint of different contents dealing with the space, teaching tools and supporting instruments they use. Based on the results of the survey the author suggests the possibilities of future development of education regarding the teaching about the values of space, sustainable development and public awareness of them.
Keywords: geografija; geography; prostor; sustainable development; trajnostni razvoj; regionalni razvoj; school; šolstvo; education; izobraževanje; učila; učni pripomočki; metodika pouka; Europe; Evropa; Slovenia; Slovenija